Manca': A Study of the Martial Arts' Symbol as Makassar Cultural Identity in Gowa, South Sulawesi - Mutahhar Syan; Supriadi Hamdat (ETNOSIA : Jurnal Etnografi Indonesia, 2019)
This study aims to describe and analyze the symbols of movements and costumes used from martial arts as a cultural identity that is present and attached to the Sulawesi Pencak Silat Association (IPS). The study used a qualitative descriptive approach with ethnographic methods. This research was conducted in Padepokan Pencak Silat Sulawesi Association (IPS) in Taeng Village, Gowa Regency. The analysis technique used is symbolic interpretation, which sees symbols and meanings going hand in hand from each movement used. This research shows that silat or manca tidak is not talking about stance as a form of organized movement, but rather on the functions, benefits, risks posed. The parts of silat contain meanings and symbols that are understood as cultural identity and forms of belief, namely: the fingers describe three in one form of respect, stepping with the right foot first, the foot is always shaped like an easel.